About the single system of protection classes of elements of critical information infrastructure by the criteria of importance and information security - O. Kalashniov, Andey; F. Mik halevich, Igor (International Journal of Engineering and Technology, 2018)
In work on the basis of integration of criteria of elements of importance for critical information infrastructure and information security, and single network security trust model, a single system of protection classes of elements of critical information infrastructure is developed.Â Â